2007
DOI: 10.1099/vir.0.82667-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular biology of potexviruses: recent advances

Abstract: Recent advances in potexvirus research have produced new models describing virus replication, cell-to-cell movement, encapsidation, R gene-mediated resistance and gene silencing. Interactions between distant RNA elements are a central theme in potexvirus replication. The 59 non-translated region (NTR) regulates genomic and subgenomic RNA synthesis and encapsidation, as well as virus plasmodesmal transport. The 39 NTR regulates both plus-and minus-strand RNA synthesis. How the triple gene-block proteins interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(93 citation statements)
references
References 125 publications
(192 reference statements)
2
82
0
9
Order By: Relevance
“…Previous studies have examined intracellular localization and interactions of the TGB proteins of several potexviruses through expression of individual gene fusion constructs by biolistic delivery to epidermal cells or expression from modified viral genomes (reviewed by Morozov & Solovyev, 2003;Verchot-Lubicz, 2005;Verchot-Lubicz et al, 2007). In contrast, we have utilized Agrobacterium-mediated infiltration to deliver TGB fusion constructs throughout the leaf, and, in confirmatory experiments, expressed AltMV TGB3 variants as additional genes from both AltMV and PVX infectious clones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have examined intracellular localization and interactions of the TGB proteins of several potexviruses through expression of individual gene fusion constructs by biolistic delivery to epidermal cells or expression from modified viral genomes (reviewed by Morozov & Solovyev, 2003;Verchot-Lubicz, 2005;Verchot-Lubicz et al, 2007). In contrast, we have utilized Agrobacterium-mediated infiltration to deliver TGB fusion constructs throughout the leaf, and, in confirmatory experiments, expressed AltMV TGB3 variants as additional genes from both AltMV and PVX infectious clones.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this body of work, 'a full understanding of the specific requirement of TGB3 and the functional interchangeability of TGB3 among different potexviruses for intercellular movement remains elusive' (Lin et al, 2006). The 8 kDa PVX TGB3 is an ER-binding protein with a single, N-terminal transmembrane domain (Morozov & Solovyev, 2003;Verchot-Lubicz et al, 2007), and TGB2 and TGB3 are reported to co-localize (Ju et al, 2008;Solovyev et al, 2000). PVX TGB3 interacts with the ER network and is associated with granular vesicles induced by TGB2 (Samuels et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PVX is the type member of the Potexvirus family of viruses (Verchot-Lubicz et al, 2007). Although the PVX VSR, P25, destabilizes Arabidopsis AGO1, this virus does not normally systemically infect Arabidopsis Columbia-0 (Col-0) (Chiu et al, 2010;Jaubert et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the genus Potexvirus have a monopartite, positive-strand RNA genome containing five open reading frames (ORFs) (Verchot-Lubicz et al, 2007). ORF1 encodes a viral replicase and ORF5 encodes a coat protein (CP).…”
Section: Introductionmentioning
confidence: 99%